Investigation of Male External Genitalia Tracts of Brackish waters Crabs, Callinectes amnicola, (De Rochebrune, 1883) from Côte d’Ivoire - Marie Anne Kayi d’Almeida; Komenan Daouda Kouassi (Research Aspects in Biological Science Vol. 3, 2022)
Callinectes amnicola is a Crustacean species found primarily in West Africa. The crab Callinectes amnicola, which is the most exploited species in Côte d’Ivoire, is on the verge of extinction due to overfishing. The management of natural stock or breeding has become essential in order to alleviate this situation. These features entail an understanding of the reproductive organs’ structural organization and physiology. The goal of this research is to better understand the morphology and function of the reproductive system’s external organs. The identification of organs was carried out with naked eye or with binocular magnifier. Histological techniques were used to conduct microscopic examinations. Male sexual maturity is divided into seven stages, according to macroscopic findings. The penes wall is made up of a connective tissue layer, a muscle layer, an interior columnar and ciliated epithelium, and a moderately large lumen in both juvenile and mature males. The tubular long first gonopods (G1) and the shorter second pleopods (G2) are the two forms of pleopods or gonopods seen in Callinectes amnicola. The first gonopod (G1) is made up of coxopodite XIII, a subterminal segment, and a tube-like terminal segment or telopodite. The tube or groove has apical and basal openings. Gonopods are connected by a calcified wall that surrounds bundles of striated muscle fibers and glandular regions. The coxopodite XIV, a medial part, and the apical spine make up the second gonopod (G2). It is inserted into the first pleopod’s posterior foramen and drives semen and spermatophores via the first pleopod’s groove. The external tract’s physiology was studied. The mechanical organs of copulation are the penis and first pleopods.